Causes Won, Lost, and Forgotten : How Hollywood and Popular Art Shape What We Know about the Civil War - Gallagher, Gary W. (Book collections on Project MUSE., 2008)
Describes how the depiction of the Civil War in motion pictures and works of art distorts the reality of the war, often emphasizing how the South fought for an admirable but hopeless cause and minimizing the Union effort to hold the republic together.